Evaluation of the inhibitory mechanism of Pennisetum glaucum (pearl millet) bioactive compounds for rheumatoid arthritis: an in vitro and computational approach - Sharif, Maria; John, Peter; Bhatti, Attya; Paracha, Rehan Zafar; Majeed, Abid (Frontiers in Pharmacology, 2024)
Introduction Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by synovial infiltration and pannus formation, and its rising incidence is significantly contributing to the global disability rate. Despite advances in biological drugs, no treatment has successfully cured or averted its progression. Consequently, natural drugs are being explored as alternative therapeutic strategies. Objective This study aims to evaluate the therapeutic potential of Pennisetum glaucum (pearl millet) and to identify its bioactive compounds to assess their effectiveness against RA targets. Methods The therapeutic potential of P. glaucum extracts was evaluated by antioxidant and anti-inflammatory assays. Gas chromatography-mass spectrometry (GC-MS) was utilized to identify the compounds in P. glaucum extract. The pharmacokinetics and safety profile of these compounds were studied by absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis. Network pharmacology, molecular docking, and molecular dynamic (MD) simulation were employed to identify the active compounds and their therapeutic targets in P. glaucum for RA treatment. Results Acidified methanol (AM) extract of P. glaucum showed the highest phenolic (213 ± 0.008 mg GAE/g DW) and flavonoid content (138.1 ± 0.03 mg RE/g DW), demonstrating significant antioxidant and anti-inflammatory potential. GC-MS of AM extract identified 223 compounds. Lipinski and toxicity parameters screened out 17 compounds. Protein–protein interaction (PPI) analysis shortlisted 20 key targets in RA pathways, nine of which were upregulated in five microarray datasets. Molecular docking and MD simulations revealed that compound-7 (benzenesulfonamide, 2-nitro-N-phenyl-) and compound-9 (Pregnane-3,20-diamine, (3.beta.,5.alpha.,20S)-) bind strongly with MMP9, JAK2, PTGS2, and HIF1a compared to the reference, predicting stable interaction with these upregulated genes. Finally, PASS (prediction of activity spectra for biological active substances) analysis further validated the anti-arthritic potential of these compounds based on their chemical structure. Conclusion This study uncovered a therapeutic drug candidate against HIF1a, MMP9, JAK2, and PTGS2 for RA from P. glaucum active compounds, laying the groundwork for future research.